PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH - NURWEDA NURWEDA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
This research is a classroom action research (Classroom Action Research) which aims to improve the learning outcomes of history subjects through the jigsaw cooperative learning model in class X students of SMK Muhammadiyah Watansoppeng. The research was carried out in the odd semester of 2021/2022 with 17 students as research subjects consisting of 9 men and 8 women. The research procedure was carried out in 4 stages, namely planning, action, observing and reflecting. The number of cycles is 2 cycles, each cycle consists of 4 meetings. Data were collected through tests and non-tests (observation and recording) for the activities that occurred during the learning of history subjects. Data were analyzed using qualitative analysis techniques and quantitative analysis. While the data validation technique was done by saturation and triangulation. The results showed that the average score of student learning outcomes in the first cycle was 70.00 and in the second cycle there was an increase of 78.53.The percentage of students' completeness in the first cycle was 64.71% and the second cycle was 94,12 %. The results of observational research indicate that there is an increase in the quality of learning activities to cycle II both in terms of attendance, activeness in learning and active involvement in working individually and in groups with home groups and expert groups. The conclusion of the research results supports the research hypothesis that through the jigsaw type cooperative learning model can improve the learning outcomes of history subjects for class X students of SMK Muhammadiyah Watansoppeng, Soppeng Regency for the 2021/2022 academic year. ABSTRAKPenelitian ini adalah penelitian tindakan kelas ( Classroom Action Research) yang bertujuan untuk meningkatkan hasil belajar mata pelajaran sejarah melalui model pembelajaran kooperatif jigsaw pada siswa kelas X SMK Muhammadiyah Watansoppeng.Penelitian dilaksanakan pada semester ganjil tahun 2021/ 2022 dengan subyek penelitian 17 siswa yang terdiri dari 9 orang laki-laki dan 8 orang perempuan. Prosedur penelitian di lakukan dengan 4 tahap yaitu planning, action, observing dan reflecting. Jumlah siklus adalah 2 siklus yang tiap siklusnya terdiri atas 4 kali pertemuan. Data di kumpul melalui tes dan non tes (observasi dan perekaman) di maksud untuk aktivitas yang terjadi selama pembelajaran mata pelajaran sejarah berlangsung. Data dianalisis dengan mengunakan teknik analisis kualitatif dan analisis kuantitatif. Sedangkan teknik validasi data dilakukan saturasi dan triannggulasi.Hasil penelitian menunjukkan bahwa skor rata-rata hasil belajar siswa pada siklus I sebesar 70,00 dan pada siklus II mengalami peningkatan sebesar 78,53. Persentase ketuntasan siswa pada siklus I sebesar 64,71% dan siklus II sebesar 94,12% . Hasil penelitian observasi menunjukkan bahwa ada peningkatan kualitas aktivitas pembelajaran ke siklus II baik dari segi kehadiran,keaktifan dalam pembelajaran serta keterlibatan aktif dalam bekerja individu maupun berkelompok dengan kelompok asal maupun kelompok ahli. Kesimpulan hasil penelitian mendukung hipotesis penelitian yaitu melalui model pembelajaran kooperatif tipe jigsaw dapat meningkatkan hasil belajar mata pelajaran sejarah siswa kelas X SMK Muhammadiyah Watansoppeng Kabupaten Soppeng tahun pelajaran 2021/2022.